SMART APPS CREATOR (EDUPRO)-ASSISTED EDUTAINMENT TO SUPPORT STUDENT LEARNING MOTIVATION ON OPPORTUNITY MATERIALS - Dini Andriyanah; Eka Farida Fasha (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Pupils' motivation to learn mathematics, particularly probability-related content, is still comparatively low. This is brought on by dry teaching strategies, low levels of student participation, and a dearth of engaging learning resources. In light of these circumstances, the goal of this study is to create edutainment-based learning materials with the use of Smart Apps Creator (Edupro) to boost grade X vocational high school students' motivation to learn about probability. The 4D development approach (Define, Design, Develop, Disseminate) is used in this form of research and development (R&D). Teachers' and students' practicality questionnaires and validation sheets from media and material specialists are among the research tools. The purpose of the evaluation was to ascertain the developed media's degree of validity and usefulness. According to the findings, Edupro media received a very valid category validation score of 92.11% from media professionals and 91.67% from material experts. 22 students scored 90% on the practicality test, which is considered very practical. As a result, the Edupro media is approved for use in mathematics classes that cover probability. According to the study's findings, Edupro media can serve as a useful substitute for encouraging students to learn. Testing its impact on learning objectives and creating comparable media for other resources are two further suggestions.